2021
DOI: 10.1111/sifp.12178
|View full text |Cite
|
Sign up to set email alerts
|

“We Don't Fear HIV. We Just Fear Walking around Pregnant.”: A Qualitative Analysis of Adolescent Sexuality and Pregnancy Stigma in Informal Settlements in Kisumu, Kenya

Abstract: In Kenya, adolescent pregnancy rates are high, contraception utilization is low, and adolescent sexuality is stigmatized. We describe how perceptions of sexuality and pregnancy stigma influence decision‐making among adolescents in the informal settlements of Kisumu. We used purposive sampling to recruit 120 adolescent boys and girls aged 15–19 for focus group discussions. A semistructured interview guide was used to elicit social norms and community attitudes about sexual and reproductive health. We analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
11
0
3
Order By: Relevance
“…In focus group discussions that were conducted as a component of our study, older adolescents were better informed about PrEP than the younger adolescents and viewed PrEP as an alternative HIV prevention tool because of their dislike of using condoms. 34 More than half of adolescents with no prior use expressed willingness to take PrEP, an encouraging finding. Previous studies have noted that adolescent sexuality stigma, which is pervasive in African culture, is as a key barrier because of fear that people who use PrEP would be perceived as promiscuous.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In focus group discussions that were conducted as a component of our study, older adolescents were better informed about PrEP than the younger adolescents and viewed PrEP as an alternative HIV prevention tool because of their dislike of using condoms. 34 More than half of adolescents with no prior use expressed willingness to take PrEP, an encouraging finding. Previous studies have noted that adolescent sexuality stigma, which is pervasive in African culture, is as a key barrier because of fear that people who use PrEP would be perceived as promiscuous.…”
Section: Discussionmentioning
confidence: 93%
“…In focus group discussions that were conducted as a component of our study, older adolescents were better informed about PrEP than the younger adolescents and viewed PrEP as an alternative HIV prevention tool because of their dislike of using condoms. 34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, their partners deny paternity and refuse to support them, which make them vulnerable to poor mental health [28,29]. Previous studies have also shown that community or neighborhood-level factors are relevant in understanding poor mental health among pregnant and parenting adolescents [30][31][32].…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…School girls in Western Kenya experiencing lockdown had twice the risk of falling pregnant compared with the pre-COVID-19 period 14. Teenage pregnancy in Kenya is considered shameful and can result in stigma against the girl and/or family, exclusion or expulsion from school and violence from partners or parents 15–18. Many teenage pregnancies in Kenya stem from consensual boyfriend–girlfriend relationships19 but patriarchal norms mean teenage fathers may not experience the same increase in vulnerability.…”
Section: Introductionmentioning
confidence: 99%